Manajemen Kualitas dan Kepuasan Pelanggan: Sebuah Systematic Literature Review pada Organisasi Bisnis, Pendidikan dan Perikanan - Wardatul Kamilah; Nadia Yolanda Salsabila; Adellia Rizky Falela; Mu’allimin Mu’allimin (Lembag, 2025)
Quality management has become an increasingly strategic issue across various sectors, including business, education, and fisheries, as it directly relates to customer satisfaction, competitiveness, and organizational sustainability. However, the existing literature reveals diverse approaches and outcomes, necessitating a more comprehensive synthesisThis research seeks to analyze the influence of quality. management in improving organizational performance, customer satisfaction, and sustainability. Using a qualitative literature review method, the search process was conducted through Google Scholar and the Publish or Perish application with the keyword “Customer Satisfaction.” From the initial 30 articles published between 2020 and 2025, 27 were screened and validated, and 5 core articles were selected for in-depth analysis. The findings reveal three major insights. First, the implementation of Total Quality Management (TQM) enhances organizational culture, performance, and competitiveness. Second, quality management in the fisheries sector plays a vital role in water quality control, supporting successful production outcomes. Third, product and service quality emerge as dominant factors influencing customer satisfaction and loyalty. In conclusion, quality management serves as a fundamental and cross-sectoral strategy that strengthens organizational performance and sustainability. Future studies are encouraged to explore the integration of quality management with digital transformation and environmental sustainability to develop more adaptive and resilient management models suited to the evolving global context.